PERSEPSI AUDITOR EKSTERNAL DAN AUDITOR INTERNAL PEMERINTAH MENGENAI EFEKTIVITAS METODE RED FLAGS DALAM MENDETEKSI FRAUD PELAPORAN KEUANGAN BUMD - Pangihutan Siallagan; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2017)
This study aims to Know and obtain empirical evidence about the perception of the external auditor and the internal auditor of government regarding the effectiveness of the effectiveness of red flags in detecting fraudulent financial reporting of Regional-Owned enterprises.            This research was conducted by questionnaire to the Indonesian government external auditors and Indonesian government internal auditors using Likert scale. Sampling technique used the random sampling. There are 95 respndents, 54 external auditors works in Indonesian Supreme Audit Institution and 41 internal auditors works in State Development Audit Agency.  Analysis of this hypothesis using Independent Sample t-Test to determined whether two samples of unrelated had an average of different and compare the average two groups that do not relate to each other.            The results showed that there was no significant difference between the perception of Indonesian government external auditors and Indonesian government internal auditors regarding the effectiveness of red flags in the category of Pressure, Opportunity, and rationalization in detecting fraudulent financial reporting of -Owned enterprises. The results also show that the category of red flags that are most effective in detecting fraudulent financial of Regional-Owned enterprises is a red flag on the category opportunity